Correlation between genital infections and cervical cytopathological changes in patients assistedin Porto Alegre Public Health System - Becke, Débora L; Brochier, Andressa W; Vaz, Cristiane B; Oliveira, Julyana P; Santos, Maria de Lourdes V; Pilger, Diogo André; Calil, Luciane; Fuentefria, Alexandre M (Brazilian Journal of Sexually Transmitted Diseases, 2011)
Introduction: cervical cancer has been considered the second most common malignancy among women, and is often associated with infectious agents (AI) related to sexually transmitted diseases (STDs) or opportunistic of genitourinary tract. Objective: to evaluate the epidemiological variables and correlate them with cytological benign and malignant cervical changes, as well as the prevalence of AI found in cytology preventive exam. Methods: retrospective analysis of cytological reports issued between 2004 and 2009 of patients treated in 33 Basic Health Care Units in Porto Alegre. A total of 850 reports were selected from different patients and the following variables were analyzed: age, education, AI and cellular changes. Results: approximately 70% of women are at the age between 14 and 45 years old, mainly with incomplete primary school (38.4%). The infectious agent that had the highest prevalence was Gardnerella vaginalis with 15.6% followed by Candida sp. (2.3%) and Trichomonas vaginalis (2.2%). Among the benign cervical cell changes with the highest prevalence was inflammatory epithelium (67%), mostly observed in the youngest age group. A statistically significant correlation between the benign cervical cell changes with infectious agents and with age was obtained, and of 275 cases of inflammation, 161 (58.5%) had also some AI. Regarding to malignant cell changes, few cases were detected; it is not possible to obtain any correlation. Conclusion: the results observed in this study suggest that there is a correlation of cytological changes in cervical-vaginal benign cases with previous or concomitant microbial infections in women evaluated in this study.